2010
DOI: 10.1111/j.1365-3180.2009.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding spring wheat for improved allelopathic potential

Abstract: It is becoming apparent that allelopathy plays a significant role in the competitive ability of cereals against weeds; barley, wheat and rice cultivars with high allelopathic activity have been identified. However, direct breeding efforts to improve allelopathy have to date only been reported in rice. In this study, a breeding programme in spring wheat (Triticum aestivum) was evaluated to determine the efficiency of selection of allelopathy and the ability of breeding lines to suppress weeds in the field. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 21 publications
0
52
1
3
Order By: Relevance
“…If early vigour is also improved to the level of triticale, weed biomass could be reduced by 40% -60%. In spring wheat, an improvement of PAAr by 20% resulted in an average reduction in weed biomass of four near isogenic breeding lines by 19% [41]. Some of the wheat-rye substitution lines showed a PAA value as high as 63%.…”
Section: Genetic Genesmentioning
confidence: 99%
“…If early vigour is also improved to the level of triticale, weed biomass could be reduced by 40% -60%. In spring wheat, an improvement of PAAr by 20% resulted in an average reduction in weed biomass of four near isogenic breeding lines by 19% [41]. Some of the wheat-rye substitution lines showed a PAA value as high as 63%.…”
Section: Genetic Genesmentioning
confidence: 99%
“…However, any increase in weed suppression by breeding is likely to impair grain yield and subsequently rice productivity. Although a certain yield reduction may be accepted if weed competitive ability is improved sufficiently to reduce other weed management options,29 the relationship between grain yield and weed suppression needs to be identified under field conditions. This study reports on crosses between allelopathic rice PI312777 and commercial Chinese cultivars (N2S, N9S, Huahui354, Peiai64S and Tehuazhan35) to develop commercially acceptable allelopathic rice cultivars using traditional breeding methods.…”
Section: Introductionmentioning
confidence: 99%
“…Weed competitiveness and the ability to establish symbiont relations with micro-organisms in the soil are relevant for OF because they can enhance the uptake of resources and its use efficiency [27,29]. Research has shown that there exists genetic variation for weed competitiveness in cereals [30][31][32][33], and that early vigor and allelopathy can be useful traits to enhance weed suppression [30,34].…”
Section: Traits and Sources Of Variationmentioning
confidence: 99%